SUCNR1 Mediates the Priming Step of the Inflammasome in Intestinal Epithelial Cells: Relevance in Ulcerative Colitis - Bauset, Cristina; Lis-Lopez, Lluis; Coll, Sandra; Gisbert-Ferrándiz, Laura; Macias-Ceja, Dulce C.; Seco-Cervera, Marta; Navarro, Francisco; Esplugues, Juan V.; Calatayud, Sara; Ortiz-Masia, Dolores; Barrachina, Maria D.; Cosín-Roger, Jesús (Biomedicines, 2022)
Intestinal epithelial cells (IECs) constitute a defensive physical barrier in mucosal tissues and their disruption is involved in the etiopathogenesis of several inflammatory pathologies, such as Ulcerative Colitis (UC). Recently, the succinate receptor SUCNR1 was associated with the activation of inflammatory pathways in several cell types, but little is known about its role in IECs. We aimed to analyze the role of SUCNR1 in the inflammasome priming and its relevance in UC. Inflammatory and inflammasome markers and SUCNR1 were analyzed in HT29 cells treated with succinate and/or an inflammatory cocktail and transfected with SUCNR1 siRNA in a murine DSS model, and in intestinal resections from 15 UC and non-IBD patients. Results showed that this receptor mediated the inflammasome, priming both in vitro in HT29 cells and in vivo in a murine chronic DSS-colitis model. Moreover, SUNCR1 was also found to be involved in the activation of the inflammatory pathways NFкB and ERK pathways, even in basal conditions, since the transient knock-down of this receptor significantly reduced the constitutive levels of pERK-1/2 and pNFкB and impaired LPS-induced inflammation. Finally, UC patients showed a significant increase in the expression of SUCNR1 and several inflammasome components which correlated positively and significantly. Therefore, our results demonstrated a role for SUCNR1 in basal and stimulated inflammatory pathways in intestinal epithelial cells and suggested a pivotal role for this receptor in inflammasome activation in UC.